Beetle horns and horned beetles: emerging models in developmental evolution and ecology. (30th July 2012) - Kijimoto, Teiya; Pespeni, Melissa; Beckers, Oliver; Moczek, Armin P.
Abstract: Many important questions in developmental biology increasingly interface with related questions in other biological disciplines such as evolutionary biology and ecology. In this article, we review and summarize recent progress in the development of horned beetles and beetle horns as study systems amenable to the integration of a wide range of approaches, from gene function analysis in the laboratory to population ecological and behavioral studies in the field. Specifically, we focus on three key questions at the current interface of developmental biology, evolutionary biology and ecology: (1) the developmental mechanisms underlying the origin and diversification of novel, complex traits, (2) the relationship between phenotypic diversification and the diversification of genes and transcriptomes, and (3) the role of behavior as a leader or follower in developmental evolution. For each question we discuss how work on horned beetles is contributing to our current understanding of key issues, as well as highlight challenges and opportunities for future studies. WIREs Dev Biol 2013, 2:405–418. doi: 10.1002/wdev.81 This article is categorized under: Comparative Development and Evolution > Organ System Comparisons Between Species Comparative Development and Evolution > Regulation of Organ Diversity Comparative Development and Evolution > Evolutionary Novelties Technologies > Perturbing Genes and Generating Modified Animals